Attenuated Salmonella typhimurium delivering DNA vaccine encoding duck enteritis virus UL24 induced systemic and mucosal immune responses and conferred good protection against challenge - Yu Xia (Veterinary Research, 2012)
Abstract Orally delivered DNA vaccines against duck enteritis virus (DEV) were developed using live attenuated Salmonella typhimurium (SL7207) as a carrier and Escherichia coli heat labile enterotoxin B subunit (LTB) as a mucosal adjuvant. DNA vaccine plasmids pVAX-UL24 and pVAX-LTB-UL24 were constructed and transformed into attenuated Salmonella typhimurium SL7207 resulting SL7207 (pVAX-UL24) and SL7207 (pVAX-LTB-UL24) respectively. After ducklings were orally inoculated with SL7207 (pVAX-UL24) or SL7207 (pVAX-LTB-UL24), the anti-DEV mucosal and systemic immune responses were recorded. To identify the optimum dose that confers maximum protection, we used different doses of the candidate vaccine SL7207 (pVAX-LTB-UL24) during oral immunization. The strongest mucosal and systemic immune responses developed in the SL7207 (pVAX-LTB-UL24) (1011 CFU) immunized group. Accordingly, oral immunization of ducklings with SL7207 (pVAX-LTB-UL24) showed superior efficacy of protection (60-80%) against a lethal DEV challenge (1000 LD50), compared with the limited survival rate (40%) of ducklings immunized with SL7207 (pVAX-UL24). Our study suggests that the SL7207 (pVAX-LTB-UL24) can be a candidate DEV vaccine.